Case report: Significant quantitative MRI brain volumetric finding associated with electrical brain injury - Annah Ramones; Andrew Pita; David Keator; Joseph Wu (Elsevier, 2018)
Electrical injury (EI) occurs when current comes in contact with the body, and can result in skin burns, tissue damage, respiratory arrest, and death in some cases. Many EI patients experience neuropsychological deterioration and show symptoms of memory problems, post-traumatic stress disorder (PTSD), sensory disturbances, depression, and other cognitive deficits. In this study, we present the uncommon case of a 43-year-old male with a statistically significant increase in his right lateral ventricle after coming into contact with stray voltage. Upon injury, he sustained retrograde amnesia and first-degree burns on his right underarm and on the dorsal aspect of both forearms; the total surface area affected was 3.3%. One month later, he began experiencing anxiety, depression, memory problems, PTSD, and insomnia, all of which persisted up to at least six years after the electrical injury. The patient's magnetic resonance imaging scans were used to perform quantitative volumetric analysis and identify various regions of interest that were statistically significant against Functional Biomedical Informatics Research Network (FBIRN) controls. We ran a two-sample t-test of the patient against FBIRN controls (n = 42, mean age = 34.12 years, SD = 11.02 years, females = 14, males = 28) with gender and age as covariates. Regions of interest were identified (P < 0.5) using the contrasts generated in the two-sample t-test, and fractional anisotropy values were extracted from the patient and male controls (n = 15, mean = 41.47 years, SD = 8.22 years). We found an increase in the patient's right lateral ventricle 2 standard deviations above the mean value of the controls, consistent with right-sided fractional anisotropy abnormalities found in the statistical comparison. Keywords: Electrical brain injury, Magnetic resonance imaging, MRI, Diffusion tensor imaging, DTI, Quantitative volumetric, Electrical injury